PENANAMAN NILAI-NILAI ISLAM PADA ANAK USIA DINI DI WILAYAH PESISIR DESA BONEATIRO KECAMATAN KAPONTORI KABUPATEN BUTON - Risman, Kadar; Henny, Henny; Susanto, Aris; Saleh, Rachman; Salsabila, Nanda (LPPM Institut Pendidikan Nusantara Global, 2022)
Community Service which the author carried out with the team on October 19, 2022, at Boneatiro Village, Kapuntori District, Buton Regency aims to provide knowledge, understanding, and development of insight to the community, especially parents who work as fishermen regarding fostering Islamic values from an early age. The target of the service is parents who have early childhood and parents who work as fishermen. The problem with community service is the lack of knowledge and attention of parents in instilling Islamic values in their children from an early age. The author and the Community Service team raised the theme of Early Childhood Education as a Pillar of Building a Progressive Village. From this theme, the PkM Team broke it down into 2 discussion materials presented at the seminar, namely: 1) The Importance of Early Childhood Education in Coastal Areas (Children Fishermen), 2) Inculcation of Islamic Values in Early Childhood in the Area coast. There are 3 stages that are passed in the dedication process, namely the preparation stage, the implementation stage, and the evaluation stage. The preparatory stage is carried out by making observations as a preliminary step to see the real conditions that occur in the coastal community environment. The implementation stage is the stage of assisting the material that has been prepared by the author with the lecture and discussion method. The stage ends with an evaluation. Evaluation is carried out by collecting and concluding the information and data obtained at the stages carried out. The results of the seminar showed an increase in parents' knowledge and understanding of the importance of fusing Islamic values in children from an early age, this knowledge and understanding were responded to by parents' strong commitment to implementing it in everyday life.